Search for heavy resonances decaying to a top quark and a bottom quark in the lepton+jets final state in proton–proton collisions at 13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Elsevier, 2018)
A search is presented for narrow heavy resonances decaying to a top quark and a bottom quark using data collected by the CMS experiment at √s = 13 TeV in 2016. The data set analyzed corresponds to an integrated luminosity of 35.9 fb−1. Final states that include a single lepton (e, μ), multiple jets, and missing transverse momentum are analyzed. No evidence is found for the production of a W boson, and the production of right-handed W bosons is excluded at 95% confidence level for masses up to 3.6 TeV depending on the scenario considered. Exclusion limits for W bosons are also presented as a function of their coupling strength to left- and right-handed fermions. These limits on a W boson decaying via a top and a bottom quark are the most stringent published to date.